Informal Identification of Student Learning Styles by Primary School Teachers: Insights from a Qualitative Study: Informal Identification of Student Learning Styles by Primary School Teachers: Insights from a Qualitative Study - Sitokkonni, Joice; Fitriyani; Widya; Abduh, Amirullah (International Journal of Language, Education, and Literature, 2025)
This study explores how primary school teachers informally identify and categorize students’ learning styles in the classroom. While learning style theories such as Fleming’s VARK model are widely known, their practical application in primary education often lacks formal support or diagnostic tools. In the context of Indonesia’s Kurikulum Merdeka, where differentiated instruction is encouraged, teachers are expected to address diverse student learning needs. However, little is known about how teachers recognize learning preferences in everyday classroom practice. This study employed a qualitative descriptive approach and involved six teachers from IBC School Makassar. Data were collected through classroom observations and semi-structured interviews, then analyzed using Miles and Huberman’s interactive model. The findings revealed that teachers used informal strategies such as observing student behavior, participation patterns, and task preferences to identify visual, auditory, reading/writing, and kinesthetic learners. Although no formal instruments were used, teachers demonstrated intuitive awareness of students’ learning preferences and adjusted their teaching accordingly. Most teachers adopted a multimodal approach, reflecting the overlap and fluidity of learning styles among students. These results suggest that informal identification methods, while flexible and contextually effective, could be strengthened by institutional training and support systems. The study contributes to a deeper understanding of teacher-led learning differentiation and highlights the importance of perception-based strategies in inclusive classroom environments.